The Effect of Interval Training on Increasing VO2Max and Hemoglobin Levels in Central Java PPLOP Athletes - Dhuha, Ahad Agafian; Yogaswara, Andre; Hajar, Nabil; Firdaus, Mohammad Fajar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Semarang, 2024)
Background: In adolescence, the level of anemia is very high so it is feared that it can affect athlete performance, while athletes must have high hemoglobin levels to support their performance in training and competing. This study also aims to determine methods for increasing hemoglobin levels besides using iron-rich foods. Method: This study uses an experimental method with independent variables interval training and dependent variables VO2Max and hemoglobin levels. The population in this study were PPLOP Central Java karate athletes, the sampling technique used was total sampling. The test instrument used to measure VO2Max was the Balked test and the test instrument to measure hemoglobin was the HemoCue blood photometer. Result: the results in this study interval training can increase VO2Max with an average increase of 1.73% and interval training can increase hemoglobin levels by an average of 5.98 gr/dl. Conclusion: interval training can be used as a reference for increasing VO2Max and hemoglobin levels, for optimal increases can be accompanied by consumption of foods high in iron.